Tauzī‘ wa Tanwī‘ Bunūd As'islah Ikhtibār An-Nahw li-shaff Ats-Tsālis Al-mutawašithah: Distribution and Diversification of Arabic Grammar Test Items for The Third Grade of Junior High School - Ibnu Hafid Alfarisy; Moh. Ainin; Moh. Khasairi (Jurusan Pendidikan Bahasa Arab UIN Sunan Kalijaga, 2023)
In preparing the test items, the test maker must take care of using suitable type of test items and diversifying it. Each test item has criteria, advantages, and disadvantages that need to be considered. This research aims to reveal the distribution and diversification of Arabic grammar test items for the third grade in the Junior High School in Batu City. The research is qualitative and descriptive, as it describes the research sample according to a theory and reveals the hidden phenomena. The primary research sample is the Arabic grammar test items for the third grade of Junior High School in the 2019-2020 school year that include the contents taken from the textbook